The Relationship between Students' Bonding to School and Multiple Health Risk Behaviors among High School Students in South-East of Iran. - Farokh Abazari; Aliakbar Haghdoost; Abbas Abbaszadeh (Tehran University of Medical Sciences, 2014)
School is the first social institution which affects adolescents' lives, and it determines their opportunities, life quality and behavior. Thus, the aim of this study was to determine the relationship between students' bonds with their school and multiple health risk behaviors amongst high school students in Kerman City, Iran.In this cross-sectional study, high school students of all levels participated during November and December 2001 in Kerman. The research sample included 1024 students (588 females and 436 males) aged 15 to 19 years. A CTC (Communities That Care Youth Survey) questionnaire was designed based ona standard questionnaire in order to collect a profile of students' risk behaviors. A multi-stage cluster sampling method was used to collect the data.In the final multivariate logistic regression, two variables including; age, (ORa=1.15, P=0.02) and male gender (ORa=2.14, P=0.001) had a significant positive association with multiple health risk behaviors (MHRB). School commitment (ORa=0.38, P=0.001) and school rewards for involvement (ORa=0.80, P=0.21), had a significant negative association with MHRB.Our results quantified the pivotal role of schools in shaping the risky behavior of students. It seems that school may minimize the risky behaviors by creating a strong link, and improving the effective communications with students.